Sustainable Engineering Proceedings of EGRWSE 2018 - Agnihotri, Arvind Kumar; Reddy, Krishna; Bansal, Ajay.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume contains selected papers presented during the International Conference on Environmental Geotechnology, Recycled Waste Material and Sustainable Engineering (EGRWSE-2018). The multidisciplinary articles in this volume discuss environment-friendly technologies and the application of 'smart' solutions and initiatives to improve infrastructure and services, with a strong emphasis on sustainability and conservation of resources. This volume will be of interest to engineers, professionals, and researchers working on improving urban infrastructure and strengthen civic amenities in a sustainable manner. .
Application of response surface methodology to optimize the reaction parameters for grafting of cellulosic fiber -- Bioregeneration of granular activated carbon adsobred with analytical grade hydroquinone compound using mixed bacterial culture -- Bearing Capacity improvement of Sand Bed Reinforced with 3D Geogrids of Rectangular Pattern -- Rain Garden, A Solution to Urban Flooding: A Review -- Al-Fe and Al-Ti pillared saponite clay catalysts: Preparation and Characterization -- Performance Based Seismic Evaluation of Multi Storey R.C.C Building with Addition of Shear Wall -- Synthesis and characterization of the graft copolymers of starch for the application in packaging films -- Application of RSM for optimizing the biodiesel production catalyzed by calcium methoxide -- Synthesis and characterization of chemically derived graphene oxide from graphite.
Keywords: Engineering geology; Environmental engineering; Biotechnology; Bioremediation; Geotechnical engineering; Geoengineering; Environmental Engineering/Biotechnology.; Geotechnical Engineering and Applied Earth Sciences